2007
DOI: 10.1124/jpet.106.119156
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Optimization to Track the Antithrombotic and Hemostatic Effects of Clopidogrel in Rats

Abstract: We determined the dose response of the ADP antagonist clopidogrel (0.3-50 mg/kg p.o.) in rat models of thrombosis and provoked bleeding and correlated these activities to ex vivo platelet activation. Carotid artery thrombosis was induced by FeCl 2 . Bleeding time was measured by mesenteric vessel puncture and renal cortex or cuticle incision. Platelet biomarkers included standard ADP-induced aggregation, P2Y 12 receptor occupancy, and phosphorylation of vasodilator-stimulated phosphoprotein. Clopidogrel decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…The result was later confirmed in a prospective study, and the 50% threshold demonstrated a very high negative predictive value for MACE after PCI. 36 In a recent experimental study, Schumacher et al 37 demonstrated that a 50% PRI corresponded to a nearly 90% P2Y 12 receptor blockage. So we used 50% PRI as the cutoff point.…”
Section: Discussionmentioning
confidence: 96%
“…The result was later confirmed in a prospective study, and the 50% threshold demonstrated a very high negative predictive value for MACE after PCI. 36 In a recent experimental study, Schumacher et al 37 demonstrated that a 50% PRI corresponded to a nearly 90% P2Y 12 receptor blockage. So we used 50% PRI as the cutoff point.…”
Section: Discussionmentioning
confidence: 96%
“…It has recently been shown that levels of P2Y 12 -blockade above 60% are required to block the effects of ADP on PGE 1 -induced phosphorylation of VASP (44). Furthermore, a study in rats has shown that 90% P2Y 12 -receptor occupancy led to a PRI of 50% (45). This indicates that the VASP-P assay is insensitive to low levels of P2Y 12 -blockade (46) and might in part explain the poor specificity of the assay, which limits its value for guiding individual therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry analysis of VASP-P To measure ADP-induced platelet activation, the VASP-239 phosphorylation state was determined in citrate-anticoagulated blood samples using the PLT VASP/P2Y 12 kit, as described previously [20] . Samples were treated in accordance with the manufacturer's protocol and were analyzed within 4 h of collection.…”
Section: Creatine Kinase Mb Fraction (Ck-mb)mentioning
confidence: 99%